Review of the actualistic taphonomy of small mammals ingested by South American predators: its importance in the interpretation of the fossil record - Montalvo, Claudia Inés (2019)
In this paper, the current state of knowledge of the taphonomic characteristics of micromammal (rodents and marsupials) remains generated by the action of the different predators (avian raptors and carnivore mammals) of South America (particularly of Argentina), known through actualistic studies, is reviewed. The analyzed taphonomic attributes enabled the adjustment, by means of extensive comparisons among different groups of predators and prey, of the modification categories indicated in the original papers. The data herein revised and assessed suggest that the evaluated South American predators may be grouped into four categories of modification: a) Light (Tyto alba, Bubo virginianus, Strix chacoensis and Asio flammeus); b) Moderate (Athene cunicularia, Geranoaetus melanoleucus, Geranoaetus polyosoma and Pseudoscops clamator); c) Heavy (Circus buffoni, Caracara plancus, Elanus leucurus, Didelphis albiventris, Leopardus geoffroyi and Lontra longicaudis); d) Extreme (Milvago chimango, Puma concolor, Puma yagouaroundi, Conepatus chinga and Lycalopex griseus). Finally, the research herein discussed evaluates how these studies were applied in the fossil record of both palaeontological and archaeological sites of South America.